New data on the southern Iberian serpentinophyte flora (Andalusia, Spain) - Pérez-Latorre, Andrés Vicente; Hidalgo-Triana, Noelia; Cabezudo, Baltasar (Mediterranean Botany, 2018)
This work updates the existing list of obligate endemic serpentinophytes of the southern Iberian Peninsula. Serpentine ecosystems are developed on ultramafic outcrops which, although rare, have a worldwide distribution. The highly evolved and specialized flora that manages to inhabit these harsh ecosystems includes a very specialized and highly evolved group of plants known as serpentinophytes. Serpentinophytes are linked exclusively or almost exclusively to serpentine ecosystems. The existing list of obligate serpentinophytes (obligate endemics) which exist in the serpentine ecosystems of the southern Iberian Peninsula (Spain) consists of 22 taxa. New fieldwork has been done resulting in the description of new soil endemics and the discovery of new populations of this specialized flora. Consequently, bibliographical sources, databases such as the Global Biodiversity Information Facility (GBIF), and existing herbarium sheets have been revised. Crepis bermejana and Galatella malacitana have been added to the list and are proposed to be evaluated as threatened. Teucrium reverchonii has been excluded from the list. Euphorbia flavicoma subsp. bermejense and Armeria villosa subsp. serpentinicola required changes in nomenclature. These nomenclatural changes imply changes in population allocations. The revised list is composed of 23 obligate serpentinophyte taxa. Future conservation measures may include a complete Iberian (including Portugal) serpentinophytes checklist and corresponding revisions of States’ legislation and Red Lists.